Professional Training of the Future Teachers to the Use of Popular Folk Mobile Games in Ethno-Educatiohal Space of Primary School - Roman Dmytriv (Pedagogical Discourse, 2012)
The article describes the educational potential of games and fun and their possible use in ethnoeducatiohal space of general school. It is found out that mobile games are beneficial for health as they develop and strengthen the muscles, bring physical qualities, promote moral education and positive impact on the mental development of children.